2015
DOI: 10.1063/1.4908595
|View full text |Cite
|
Sign up to set email alerts
|

An integrated platform enabling optogenetic illumination of Caenorhabditis elegans neurons and muscular force measurement in microstructured environments

Abstract: Optogenetics has been recently applied to manipulate the neural circuits of Caenorhabditis elegans (C. elegans) to investigate its mechanosensation and locomotive behavior, which is a fundamental topic in model biology. In most neuron-related research, free C. elegans moves on an open area such as agar surface. However, this simple environment is different from the soil, in which C. elegans naturally dwells. To bridge up the gap, this paper presents integration of optogenetic illumination of C. elegans neural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Deflections and strength measurements were obtained using standard NemaFlex processing protocol, which involves automated tracking of the deflectable pillars (Fig. 7E) (Ghanbari et al, 2012; Johari et al, 2013; Khare et al, 2015; Qiu et al, 2015). Pillar deflection values extracted during image processing were converted to forces using Timoshenko beam deflection theory (Etheridge et al, 2015; Rahman et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Deflections and strength measurements were obtained using standard NemaFlex processing protocol, which involves automated tracking of the deflectable pillars (Fig. 7E) (Ghanbari et al, 2012; Johari et al, 2013; Khare et al, 2015; Qiu et al, 2015). Pillar deflection values extracted during image processing were converted to forces using Timoshenko beam deflection theory (Etheridge et al, 2015; Rahman et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, two devices were reported that contained micro-pillar structures for measuring the forces exerted by worms on their microenvironment [ 46 , 47 ]. Johari et al [ 46 ] used PDMS pillar elastic deflection concept to measure the force, and found that despite changes in the placements of pillars in a “honeycomb” or “lattice” configuration, worms continued to move in a sinusoidal pattern but their locomotion speed, undulation frequency, and body force changed significantly.…”
Section: Microfluidic Devices To Assist With Specialized Assaysmentioning
confidence: 99%
“…Measurement of forces applied on pillars revealed that the mid-body region generates the maximum force. The device by Qiu et al [ 47 ] was designed to expose worms to a particular frequency of light that they tend to avoid and measure force generated during forward or backward movements, or omega turns in the structured environment. A LabVIEW program (National Instruments, Austin, TX, USA) was also developed to assist with image capture and data analysis.…”
Section: Microfluidic Devices To Assist With Specialized Assaysmentioning
confidence: 99%
“…Locomotion. Owing to the precision achievable by microlithographic techniques, researchers have been able to investigate in-depth different locomotion patterns (by varying the size and spacing of posts), applied muscular forces (by measuring the deflection of posts) ( Figure 1D) and motility quantification (time-averaged kinetic power over the swimming cycle) [81][82][83][84][85][86][87][88][89][90]. In contrast to traditional experimental techniques, these systems permitted straightforward dynamic force detection of moving nematodes.…”
Section: Behavioral Studies Of C Elegans's Responses To Different Stmentioning
confidence: 99%